Substrate-labeled fluorescent immunoassay for measuring dibekacin concentrations in serum and plasma. - Place, J D (1983)
We have developed a homogeneous substrate-labeled fluorescent immunoassay for the measurement of dibekacin concentrations in serum and plasma. The fluorogenic enzyme substrate beta-galactosyl-umbelliferone was covalently attached to tobramycin, an aminoglycoside structurally similar to dibekacin, to prepare a fluorogenic drug reagent (FDR). The FDR is nonfluorescent under assay conditions, but fluoresces upon hydrolysis by beta-galactosidase. However, binding of the FDR by antiserum to the cross-reactive drug kanamycin prevents enzyme hydrolysis. The fixed level of FDR competes with dibekacin within the sample for the limiting number of antibody-binding sites in the reaction mixture. Unbound FDR is hydrolyzed by beta-galactosidase to release a fluorescent product that is proportional to the dibekacin concentration in the sample. The assay exhibits good precision, standard curve reproducibility, recovery, sensitivity, and correlation with a comparative method. Additionally, the substrate-labeled fluorescent immunoassay is rapid and easy to perform.